Pendidikan Berbasis Stake Holders Teori dan Implikasinya pada Manajemen Perguruan Tinggi - Mu'ammaroh, Nurul Lail Rosyidatul (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
Universities are still in the process of transitioning to the global level; therefore universities require autonomy, accountability, legitimacy, and credibility. The backwardness of the education sector must be pursued by improving the education system, and higher education as an organization must be able to adapt to these changes so as not to suffer from increasingly fierce competition. One significant effort is to reform education through innovation and creativity. Consequently, the above needs and the objectives of implementing higher education, it requires that the management of higher education institutions be carried out professionally. This can be realized when the college has an excellent strategic management plan because with proper planning the organization will be able to walk towards achieving its goals and sustainability, as well as the function of the institution as a protected educational institution. The implementation of higher education based on stakeholders inevitably must have a plan for a sustainable organizational and educational activity strategy, in accordance with the conditions of the internal environment and the external environment (competition with similar universities, regulators, inflation/ economic conditions, etc.) so that universities always have excellence competitiveness, added value and differentiation to satisfy stakeholders, which in turn make the acceptance of higher education continuously exist, respected and needed by the community.